Midrash unbound : transformations and innovations - Fishbane, Michael A.; Weinberg, Joanna (Littman library of Jewish civilization (Series), 2013)
Midrash is arguably the most ancient genre of Jewish literature, forming a voluminous body of scriptural exegesis over the course of centuries. There is hardly anything in the ancient rabbinic universe that was not taught through this medium. The diversity and development of that creative profusion are presented here in a new light. The contributors cover a broad range of texts, from late antiquity to the modern period and from all the centres of literary creativity, including non-rabbinic and non-Jewish literature, so that the full extent of the modes and transformations of Midrash can be fully appreciated. A comprehensive introduction situates Midrash in its historical and cultural setting, pointing to creative adaptations within the tradition and providing a sense of the variety of genres and applications discussed in the body of the book. Bringing together an impressive array of the leading names in the field, the volume is innovative in both its scope and content, seeking to open a new period in the study of Midrash and its creative role in the formation of culture. It should be of interest to all scholars of Jewish studies, as well as to a wider readership interested in the interrelationships between hermeneutics, culture, and creativity, and especially in the afterlife of a classical genre and its ability to inspire new creativity in many forms. Contributors: Philip Alexander, Sebastian Brock, Jacob Elbaum, Michael Fishbane, Robert Hayward, William Horbury, Sara Japhet, Ephraim Kanarfogel, Naftali Loewenthal, Ivan G. Marcus, Alison Salvesen, Marc Saperstein, Chava Turniansky, Piet van Boxel, Joanna Weinberg, Benjamin Williams, Elliot Wolfson, Eli Yassif.